Serological and Molecular Prevalence of Toxoplasma gondii among HIV-infected Pregnant Women in Calabar, Nigeria (African Journal of Biomedical Research, 2023)
Toxoplasma gondii infection (Toxoplasmosis) is a zoonotic parasitic infection that affects about 60% of the human population globally causing congenital, ocular, and cerebral infections in HIV-infected and other immunocompromised people. Morbidity and mortality data on toxoplasmosis as a congenital or as an opportunistic infection, especially among the HIV-infected subjects are lacking in the study area. The serological and molecular prevalence of toxoplasmosis in HIV-infected pregnant women in Calabar, Nigeria was investigated using a descriptive cross-sectional study. Blood samples randomly collected from one hundred and eighty (180) HIV infected and forty-five (45) non-HIV infected pregnant women, aged 10-50 years, were tested for anti-IgM and anti-IgG antibodies based on Enzyme Linked Immunosorbent Assay (ELISA) technique. Fifty samples positive for both IgM and IgG antibodies were selected and amplified by Polymerase Chain Reaction (PCR). The molecular and serological prevalence of toxoplasmosis were 50% and 52.8% respectively. There was no statistically significant association between Toxoplasma seropositivity and HIV status as seroprevalence of T. gondii among HIV infected pregnant women and their non-HIV infected pregnant counterpart were similar 52.8% vs 53.3%, respectively (P= 0.998). The highest seroprevalence, of 100% was recorded in those aged 50 years and above, while the least was seen in those aged 10-19 years, indicating seroprevalence to be age related (P0.05). This study has confirmed high prevalence of toxoplasmosis among HIV and non-HIV infected pregnant women alike in Calabar. Intensive health education, routine diagnosis using ELISA antigen/antibody technique/prophylactic treatment for toxoplasmosis in all pregnant women and screening of new-borns for the true burden of congenital toxoplasmosis and a break in the zoonotic transmission cycle are recommended.